REPRODUCTIVE AND LIPID CYCLES IN THE ATYID PRAWN CARIDINA RAJADHARI (BOUVIER) - Victor, B (Indian Journal of Fisheries, 2011)
The atyid prawn Caridina rajadhari exhibited a continuous breeding cycle with two distinct spawning seasons (October-November and February-March). Histological studies of adult females revealed a continuously active germinal zone with different maturational stages of oocytes. The continuous spermatogenic activity was evident from seasonally consistent gonad index values and successive waves of various stages of sperm differentiation. Lipid was selectively localized in the tissues of C. rajadhari and was found to be increased in ovary and hepatopancreas during spawning months. The lipid levels of testis were low, may be due to the difference in relative size of gonad. The breeding rhythm of the prawn appears to follow closely the monsoon season and greater food availability.